Raguzina L. Yu., Romanenko A. V. The problems of appropriate interpretation of slangs of D. Hammet`s creativity into Ukrainian - Raguzina L. Yu.; Romanenko A. V. (Philological Treatises, 2020)
The article deals with the problems of appropriate interpretation of slangs of D. Hammet`s creativity into Ukrainian.